Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To accurately compare the two equations provided:
Equation A: \(\sqrt{x^2+3x-6} = \sqrt{x+2}\)
Equation B: \(\sqrt[3]{x^2+3x-6} = \sqrt[3]{x+2}\)
Let's analyze them step by step:
1. Equation A:
[tex]\[\sqrt{x^2 + 3x - 6} = \sqrt{x + 2}\][/tex]
To eliminate the square roots, square both sides:
[tex]\[x^2 + 3x - 6 = x + 2\][/tex]
Rearrange the equation to bring all terms to one side:
[tex]\[x^2 + 3x - 6 - x - 2 = 0\][/tex]
Simplify:
[tex]\[x^2 + 2x - 8 = 0\][/tex]
2. Equation B:
[tex]\[\sqrt[3]{x^2 + 3x - 6} = \sqrt[3]{x + 2}\][/tex]
To eliminate the cube roots, cube both sides:
[tex]\[x^2 + 3x - 6 = x + 2\][/tex]
Rearrange the equation to bring all terms to one side:
[tex]\[x^2 + 3x - 6 - x - 2 = 0\][/tex]
Simplify:
[tex]\[x^2 + 2x - 8 = 0\][/tex]
As we can see, after eliminating the radicals and simplifying, both equations reduce to the same polynomial equation:
[tex]\[x^2 + 2x - 8 = 0\][/tex]
Now, let's consider the possible solutions:
The quadratic equation \(x^2 + 2x - 8 = 0\) can be solved using the quadratic formula:
[tex]\[x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\][/tex]
where \(a = 1\), \(b = 2\), and \(c = -8\).
Calculate the discriminant:
[tex]\[b^2 - 4ac = 2^2 - 4(1)(-8) = 4 + 32 = 36\][/tex]
Since the discriminant is positive, there are two real solutions:
[tex]\[x = \frac{-2 \pm \sqrt{36}}{2} = \frac{-2 \pm 6}{2}\][/tex]
Thus, the solutions are:
[tex]\[x_1 = \frac{4}{2} = 2\][/tex]
[tex]\[x_2 = \frac{-8}{2} = -4\][/tex]
### Verifying Extraneous Solutions:
While the solutions to the quadratic will be the same for both equations, we need to check for extraneous solutions particularly for Equation A (with square roots) since squaring both sides of an equation can introduce solutions that don't satisfy the original equation.
- For \(x = 2\):
\(\sqrt{2^2 + 3(2) - 6} = \sqrt{2 + 2}\)
\(\sqrt{4 + 6 - 6} = \sqrt{4}\)
\(\sqrt{4} = 2\)
This holds true.
- For \(x = -4\):
\(\sqrt{(-4)^2 + 3(-4) - 6} = \sqrt{-4 + 2}\)
\(\sqrt{16 - 12 - 6} = \sqrt{-2}\)
\(\sqrt{-2}\) is not a real number, so \(x = -4\) is an extraneous solution.
Equation B typically does not introduce extraneous solutions through the process of cubing both sides.
### Final Comparison:
Based on this analysis:
- Both equations \(A\) and \(B\) reduce to the same polynomial \((x^2 + 2x - 8 = 0)\) hence they have the same potential solutions.
- However, Equation A might introduce extraneous solutions due to the process of squaring both sides.
Thus, the accurate comparison of the two equations is:
Both equations have the same potential solutions, but equation A might have extraneous solutions.
Therefore, the correct answer is:
[tex]\[ \boxed{3} \][/tex]
Equation A: \(\sqrt{x^2+3x-6} = \sqrt{x+2}\)
Equation B: \(\sqrt[3]{x^2+3x-6} = \sqrt[3]{x+2}\)
Let's analyze them step by step:
1. Equation A:
[tex]\[\sqrt{x^2 + 3x - 6} = \sqrt{x + 2}\][/tex]
To eliminate the square roots, square both sides:
[tex]\[x^2 + 3x - 6 = x + 2\][/tex]
Rearrange the equation to bring all terms to one side:
[tex]\[x^2 + 3x - 6 - x - 2 = 0\][/tex]
Simplify:
[tex]\[x^2 + 2x - 8 = 0\][/tex]
2. Equation B:
[tex]\[\sqrt[3]{x^2 + 3x - 6} = \sqrt[3]{x + 2}\][/tex]
To eliminate the cube roots, cube both sides:
[tex]\[x^2 + 3x - 6 = x + 2\][/tex]
Rearrange the equation to bring all terms to one side:
[tex]\[x^2 + 3x - 6 - x - 2 = 0\][/tex]
Simplify:
[tex]\[x^2 + 2x - 8 = 0\][/tex]
As we can see, after eliminating the radicals and simplifying, both equations reduce to the same polynomial equation:
[tex]\[x^2 + 2x - 8 = 0\][/tex]
Now, let's consider the possible solutions:
The quadratic equation \(x^2 + 2x - 8 = 0\) can be solved using the quadratic formula:
[tex]\[x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\][/tex]
where \(a = 1\), \(b = 2\), and \(c = -8\).
Calculate the discriminant:
[tex]\[b^2 - 4ac = 2^2 - 4(1)(-8) = 4 + 32 = 36\][/tex]
Since the discriminant is positive, there are two real solutions:
[tex]\[x = \frac{-2 \pm \sqrt{36}}{2} = \frac{-2 \pm 6}{2}\][/tex]
Thus, the solutions are:
[tex]\[x_1 = \frac{4}{2} = 2\][/tex]
[tex]\[x_2 = \frac{-8}{2} = -4\][/tex]
### Verifying Extraneous Solutions:
While the solutions to the quadratic will be the same for both equations, we need to check for extraneous solutions particularly for Equation A (with square roots) since squaring both sides of an equation can introduce solutions that don't satisfy the original equation.
- For \(x = 2\):
\(\sqrt{2^2 + 3(2) - 6} = \sqrt{2 + 2}\)
\(\sqrt{4 + 6 - 6} = \sqrt{4}\)
\(\sqrt{4} = 2\)
This holds true.
- For \(x = -4\):
\(\sqrt{(-4)^2 + 3(-4) - 6} = \sqrt{-4 + 2}\)
\(\sqrt{16 - 12 - 6} = \sqrt{-2}\)
\(\sqrt{-2}\) is not a real number, so \(x = -4\) is an extraneous solution.
Equation B typically does not introduce extraneous solutions through the process of cubing both sides.
### Final Comparison:
Based on this analysis:
- Both equations \(A\) and \(B\) reduce to the same polynomial \((x^2 + 2x - 8 = 0)\) hence they have the same potential solutions.
- However, Equation A might introduce extraneous solutions due to the process of squaring both sides.
Thus, the accurate comparison of the two equations is:
Both equations have the same potential solutions, but equation A might have extraneous solutions.
Therefore, the correct answer is:
[tex]\[ \boxed{3} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.